2005
DOI: 10.1007/s10585-005-2669-1
|View full text |Cite
|
Sign up to set email alerts
|

A PSP94-derived Peptide PCK3145 inhibits MMP-9 Secretion and Triggers CD44 Cell Surface Shedding: Implication in Tumor Metastasis

Abstract: Our data suggest that PCK3145 may antagonize tumor cell metastatic processes by inhibiting both MMP-9 secretion and its potential binding to its cell surface docking receptor CD44. Such mechanism may involve RhoA signaling and increase in MT1-MMP-mediated CD44 shedding. Together with its beneficial effects in clinical trials, this is the first demonstration of PCK3145 acting as a MMP secretion inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…The tumor suppressor PSP94, also known as b-microseminoprotein or prostatic inhibin, is a small (10.7 kDa), non-glycosylated and cysteine-rich protein that is abundantly secreted by the prostate gland and is found in both seminal fluid and blood (Garde et al, 1999;Shukeir et al, 2003;Annahi et al, 2005;Lamy et al, 2006). It is not known how the expression of the PSP94-encoding MSMB gene is regulated.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor suppressor PSP94, also known as b-microseminoprotein or prostatic inhibin, is a small (10.7 kDa), non-glycosylated and cysteine-rich protein that is abundantly secreted by the prostate gland and is found in both seminal fluid and blood (Garde et al, 1999;Shukeir et al, 2003;Annahi et al, 2005;Lamy et al, 2006). It is not known how the expression of the PSP94-encoding MSMB gene is regulated.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…The molecular basis for the tumor-suppressor function of PSP94 is complex as this protein has been found to promote tumor cell apoptosis (Garde et al, 1999), to inhibit the secretion of a matrix metalloproteinase that is implicated in tumor metastasis (Annahi et al, 2005), and to decrease tumor-associated, vascular endothelial growth factor (VEGF)-mediated vascularization (Lamy et al, 2006). Interestingly, the antitumor effects of PSP94 can be recapitulated with a synthetic peptide comprising an N-terminal fragment of PSP94 and this peptide is currently clinically tested for the treatment of metastatic prostate cancer (Shukeir et al, 2004;Annahi et al, 2005;Lamy et al, 2006).…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…It was surprising therefore, to find that the fraction of MSMB-positive cells fell to 10% before the expression correlated with a negative outcome, suggesting that there is a redundancy in protein expression and a fraction of MSMB-expressing cells may be sufficient to maintain any potential tumor suppressing effect(s) that MSMB may exert on tumor cells. Using exogenous MSMB, in vitro and in vivo studies indicate that MSMB may have several antitumor effects on prostate tumor cells, such as suppressing growth and inducing apoptosis; [36][37][38] decreasing metastatic disease, [39][40][41] and inhibiting angiogenesis. 42 Recently, MSMB has gained further attention as a candidate for prostate cancer susceptibility gene, 20,21 and several causal risk alleles affecting the level of gene transcription have been identified in the region upstream of the coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…271 Other studies in cancer cells showed that CD44 captures MMP-2 and MMP-9 at the tumor cell surface, where MMPs then locally digest the ECM surrounding the tumor cells during extravasation. 272,273 Other MMPs might also contribute to ECM proteolysis. While conclusive in vivo proof in support of this is still missing, there are many findings that point in this direction.…”
Section: Brain Cancermentioning
confidence: 99%